2017
DOI: 10.1111/eos.12361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of application method on surface free‐energy and bond strength of universal adhesive systems to enamel

Abstract: The aim of the present study was to determine the influence of different adhesive application methods and etching modes on enamel bond effectiveness of universal adhesives using shear bond strength (SBS) testing and surface free-energy (SFE) measurements. The adhesives Scotchbond Universal, All-Bond Universal, Adhese Universal, and G-Premio Bond were used. Prepared bovine enamel specimens were divided into four groups, based on type of adhesive, and subjected to the following surface treatments: (i) total-etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
(57 reference statements)
2
22
0
1
Order By: Relevance
“…17 However in the present study, etch&rinse mode regardless of the used adhesive systems showed better results than self-etch mode in accordance with previous studies. 18,22,30,38,39 Hence the second hypothesis of the present study is accepted. Prior etching ensures a deeper penetration of the selfetch adhesives into the enamel.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…17 However in the present study, etch&rinse mode regardless of the used adhesive systems showed better results than self-etch mode in accordance with previous studies. 18,22,30,38,39 Hence the second hypothesis of the present study is accepted. Prior etching ensures a deeper penetration of the selfetch adhesives into the enamel.…”
Section: Discussionsupporting
confidence: 56%
“…Universal adhesives represent the last generation of adhesives, which can be used with different modes 21,27,28 . Various studies have investigated universal adhesives' enamel bond strength 18,20 . To the best of our knowledge, no study had been performed evaluating the bond strength values to laser-assisted bleached enamel using universal adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the different methods to determine these parameters, the approach described by Van Oss, Fowkes and Good, and Chaudhury (Neumann et al, 1974;Owens & Wendt, 1969) allows the calculation of the dispersion values, acid-base Lewis parts, polar force and hydrogen bond force, which determine the Lifshitz-van der Waals acid-base equation (Chaudhury, 1996;Good, 1992). Although the acid-base components of surface free energy of some polymeric surfaces, such as polyvinyl chloride (PVC), can exhibit some anomalies when calculated by this method, (Della Volpe & Siboni, 1997), several researchers employed it to estimate the SFE on the surface of enamel (Imai et al, 2017). This method has the same foundation of hydrophobicity angle measurement, despite hydrophobicity is measured only by angles made with water.…”
Section: Introductionmentioning
confidence: 99%